Numerical Study of Double-Diffusive Mixed Convection Flow in Channel with Hybrid Nanofluid in Porous Medium - Jaber, Karrar Kadhim; Al-Farhany, Khaled; Hamzah, Dhafer A.; Al-Kouz, Wael (Journal of Engineering and Sustainable Development, 2024)
The main objective of this work is to investigate numerically double-diffusive mixed convection flow in a channel filled with a hybrid nanofluid of Cu-Al2O3 in a porous media. It is considered that the cavity's left wall is continuously heated. The fluid flow enters the channel at low concentration and temperature. This work has been looked into two cases: Case 1, where it is supposed that the left wall cavity has high concentrations, and Case 2, where it is expected that the right wall cavity has high concentrations. The cavity's remaining walls are impermeable and thermally insulated. Non-dimension governing equations are solved with the finite element method. Parameters effects of Reynolds number(10≤Re≤100), Richardson number (2≤Ri≤10), Darcy number (Da=10-2,10-4), Lewis number (1≤Le≤5), buoyancy ratio, N=1, the solid volume fraction (ϕ=0.02),  and Prandtl number (Pr=6.2). The results show that increasing Reynolds, Richardson, and Darcy numbers increases the average Nusselt while it decreases by increasing Lewis number. In addition, Sherwood numbers increase with increasing Reynolds, Lewis, and Darcy numbers while they decrease with Richardson numbers for both cases. When the Reynolds number increases from 10 to 50 at (Da=10-4) and (Ri =10), the Nusselt number increases by 102%, while the Sherwood number decreases to 72%.